2017
DOI: 10.1186/s40425-017-0282-x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma brain metastases treated with stereotactic radiosurgery and concurrent pembrolizumab display marked regression; efficacy and safety of combined treatment

Abstract: BackgroundBrain metastases are common in patients with metastatic melanoma. With increasing numbers of melanoma patients on anti-PD-1 therapy, we sought to evaluate the safety and initial response of brain metastases treated with concurrent pembrolizumab and radiation therapy.MethodsFrom an institutional database, we retrospectively identified patients with melanoma brain metastases treated with radiation therapy (RT) who received concurrent pembrolizumab. Concurrent treatment was defined as RT during pembroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 33 publications
4
80
0
3
Order By: Relevance
“…In general, PD-L1 positive patients have a higher chance for a better [69][70][71][72][73][74][75][76][77][78][79] outcome with anti-PD-(L)1 treatment compared to PD-L1 negative patients [47][48][49]. BM seem to present a clonal population of cells distinct from those in the primary site with somatic mutations that may be driven by the brain microenvironment [50].…”
Section: Rationale and Possible Concerns For Ici-based Treatment In Bmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, PD-L1 positive patients have a higher chance for a better [69][70][71][72][73][74][75][76][77][78][79] outcome with anti-PD-(L)1 treatment compared to PD-L1 negative patients [47][48][49]. BM seem to present a clonal population of cells distinct from those in the primary site with somatic mutations that may be driven by the brain microenvironment [50].…”
Section: Rationale and Possible Concerns For Ici-based Treatment In Bmentioning
confidence: 99%
“…Furthermore, it was not mentioned whether some of these patients also received radiation during or after ICI treatment and whether this also improved efficacy [77]. In melanoma, concurrent administration defined as radiation therapy during pembrolizumab administration period and up to 4 months after most recent pembrolizumab treatment has yielded the highest intracranial ORR [78]. Furthermore, it is not clear whether the improved control of irradiated BM allows patients receiving ICI to benefit maximally from immunotherapy or whether radiation-induced cell death results in an antitumor immune response that enhances ICI.…”
Section: Combination Of Ici and Radiotherapy In Brain Metastasismentioning
confidence: 99%
“…A retrospective analysis of patients treated for brain metastases of malignant melanoma revealed that inhibition of the PD-1 axis was more effective than inhibition of CTLA-4 in combination with external beam radiotherapy and that concurrent dosing (at least 4 weeks within the two treatments) was necessary to induce best responses [163]. Independent retrospective studies and one meta-analysis confirmed these results [145,[164][165][166][167][168][169][170][171] (Table 4), also showing the superiority of combining radiation with PD-1 inhibitors compared to combination with other agents such as v-Raf murine sarcoma viral oncogene homolog B1 (BRAF) or dual specificity mitogen-activated protein kinase kinase (MEK) inhibitors [172,173] (Table 4). One retrospective study showed longer overall survival of patients irradiated more than 16 weeks after initiation of ipilimumab, compared to patients irradiated within 16 weeks of starting ipilimumab treatment [174].…”
Section: Current Clinical Insights On Irradiation and Immune Checkpoimentioning
confidence: 94%
“…According to a retrospective study, concurrent stereotactic radiosurgery (SRS) and the administration of pembrolizumab for melanoma brain metastases produces a much better response (8/23 with a complete response [CR] and 8/23 with a partial response [PR]) than SRS without concurrent immunotherapy (22%) . The addition of ipilimumab to radiotherapy significantly prolongs the survival of patients with melanoma metastasis to the brain compared with RT alone (median overall survival: 18.3 months vs. 5.3 months) .…”
Section: The Synergistic Effects Of Combinations On Patients In Preclmentioning
confidence: 99%
“…Twenty‐three patients with melanoma brain metastatic lesions were treated with concurrent SRS and pembrolizumab. Marked regression was observed (CR: 8/23 and PR: 8/23) . Concurrent durvalumab and palliative irradiation were employed to treat inoperable or metastatic cancer .…”
Section: The Role Of Radiologists In Applying the Combination Of Radimentioning
confidence: 99%